Determining the relationship between change of direction speed and agility in team sport athletes: Meta-analysis - Carvajal-Espinoza, R.; Talpey, S.; Salazar-Rojas, W. (Journal of Science in Sport and Exercise, 2025)
Background Agility and change of direction speed (COD) are essential skills in sports, their development being the focus of training and research. While these terms have been used interchangeably, it is crucial to distinguish between agility and COD, as the latter involves a sudden change in direction without the presence of external stimuli.